Transformation of the Legality of the Marriage Culture of the Samin Sambongrejo Community, Blora Regency - Hidayaht, Achmad Nur; Saipiatudin, Saipiatuddin; Kurniawan, Nandi (Universitas Veteran Bangun Nusantara, 2023)
Marriage is a sacred thing both in religion and culture when a woman and a man become legally husband and wife after carrying out the marriage contract and fulfilling the requirements and pillars of religious marriage, but the Samin people have a single rule, one man and one woman can be declared as legal partners when they become husband and wife when they first have intercourse, this is known as the pasuwitan tradition. This wedding tradition is part of the Samin people's wedding customs, but over time, many Samin people have legalized their marital status through the KUA. The procedure for the traditional Samin wedding is carried out with the stages of nakokke, mbalesi gunem, ngendek, nyuwito, ngeger, paseksen and tingkepan. Along with the development and influence of the awareness of the government and Indonesian citizens regarding the registration of marriages in Blimbing Sambongrejo Village, most of the Samin natives have legally registered their marriages and have made changes to the procedure for marriage through summons and registration of marriages at the KUA in accordance with the law as citizens. Indonesia is responsible for carrying out the obligations of the Samin people.